2013
DOI: 10.21149/spm.v55s2.5123
|View full text |Cite
|
Sign up to set email alerts
|

Violencia interpersonal en jóvenes mexicanos y oportunidades de prevención

Abstract: Objetivo. Estimar la prevalencia de daños a la salud a causa de la violencia interpersonal en adolescentes y adultos jóvenes. Material y métodos. Se presenta información sobre las consecuencias de la violencia en México. Los datos provienen de la Encuesta Nacional de Salud y Nutrición 2012 realizada entre octubre de 2011 y mayo de 2012. El análisis estadístico consistió en calcular prevalencias e intervalos de confianza al 95% para el grupo de adolescentes y jóvenes. Resultados. Cuatro de cada cien jóvenes ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
6
0
3
Order By: Relevance
“…This phenomenon may reflect a lack of current knowledge or access to recent research and/or a lack of incentives coupled with a disincentive (punishment) for the use of evidence-based practices that contradict leadership. [9,15] Another limitation of medical training in Mexico is a lack of repetitive practice inside the hospitals. The training strategy used during the intervention may have filled these gaps in the treated hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may reflect a lack of current knowledge or access to recent research and/or a lack of incentives coupled with a disincentive (punishment) for the use of evidence-based practices that contradict leadership. [9,15] Another limitation of medical training in Mexico is a lack of repetitive practice inside the hospitals. The training strategy used during the intervention may have filled these gaps in the treated hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15,16] On the contrary, there are other potentially harmful practices whose routine use is pervasive in the Mexican health system, namely, routine episiotomy, fundal pressure (Kristeller maneuver) and uterine sweeping.…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo con un informe del Banco Mundial 1 , los jóvenes en México representan cerca del 38% de las víctimas de homicidios en el país. Otros estudios también realizados en México sugieren que cuatro de cada cien jóvenes han visto afectada su salud a causa de este fenómeno 2 . En ese mismo trabajo se destaca que en varones de entre 25 y 29 años ocurren cerca de 87 homicidios por cada 100 mil habitantes.…”
Section: Introductionunclassified
“…In the case of Mexico, some studies point out that, nearly 76 percent of Mexican adolescents between 15 to 24 years old have suffered some type of violence from their partner (Alonso, 2013;Valdez-Santiago et al, 2013;González Galbán & Fernández de Juan, 2014). Rodríguez (2013) 1 found that; in Mexico 7 out of 10 youth under the age of 15 to 25 have suffered psychological or physical or sexual violence and as a consequence of these 3 out of 10 have committed suicide.…”
mentioning
confidence: 99%
“…Rodríguez (2013) 1 found that; in Mexico 7 out of 10 youth under the age of 15 to 25 have suffered psychological or physical or sexual violence and as a consequence of these 3 out of 10 have committed suicide. Similarly, Valdez-Santiago et al (2013) specifies violence among youth in Mexico has resulted serious health consequences and youth, who have faced violence are more prone to alcohol or drug abuse compared to those who never faced such violence.…”
mentioning
confidence: 99%